On‐going consequences of in utero exposure of Pb: An epigenetic perspective. Issue 10 (24th January 2022) - Tasin, Fahim Rejanur; Ahmed, Asif; Halder, Debasish; Mandal, Chanchal
Abstract: Epigenetic modifications by toxic heavy metals are one of the intensively investigated fields of modern genomic research. Among a diverse group of heavy metals, lead (Pb) is an extensively distributed toxicant causing an immense number of abnormalities in the developing fetus via a wide variety of epigenetic changes. As a divalent cation, Pb can readily cross the placental membrane and the fetal blood brain barrier leading to far‐reaching alterations in DNA methylation patterns, histone protein modifications, and micro‐RNA expression. Over recent years, several human cohorts and animal model studies have documented hypermethylation and hypomethylation of developmental genes along with altered DNA methyl‐transferase expression by in utero Pb exposure in a dose‐, duration‐, and sex‐dependent manner. Modifications in the expression of specific histone acetyltransferase enzymes along with histone acetylation and methylation levels have been reported in rodent and murine models. Apart from these, down‐regulation and up‐regulation of certain microRNAs crucial for fetal development have been shown to be associated with in utero Pb exposure in human placenta samples. All these modifications in the developing fetus during the prenatal and perinatal stages reportedly caused severe abnormalities in early or adult age, such as impaired growth, obesity, autism, diabetes, cardiovascular diseases, risks of cancer development, and Alzheimer's disease. In this review, currently available information on Pb‐mediated alterations in the fetal epigenome is summarized. Further research on Pb‐induced epigenome modification will help to understand the mechanisms in detail and will enable us to formulate safety guidelines for pregnant women and developing children. Abstract : Heavy metal toxicity is a rising issue nowadays. The developing fetus is much more vulnerable to heavy metal exposure. Pb is one of the major toxic heavy metals responsible for different epigenetic alterations (DNA methylation, histone modifications, and micro‐RNA expression) in the developing fetus. In this review, currently available information on Pb‐mediated alterations in the fetal epigenome is summarized and presented to aware people of interest.